Robust adaptive spacecraft attitude tracking control based on similar skew-symmetric structure. (November 2016) - Liu, Yi-Cheng; Zhang, Jing; Zhang, Tao; Song, Jing-Yan
Abstract: This paper addresses robust adaptive attitude tracking control for spacecrafts with unknown inertia parameters and bounded external disturbances. The similar skew-symmetric structure is chosen as the desired structure for the closed loop system when there exist no uncertainties. Based on this idea, a backstepping scheme is proposed to design the controller, and adaptive compensation and robust compensation are introduced to deal with the uncertainty of the inertia parameters and the external disturbances respectively. Theoretical analysis shows that fast response and high tracking precision can both be obtained by regulating the related parameters in the proposed controller. Simulation results are provided to demonstrate the effectiveness of the proposed attitude tracking control algorithm.